2013
DOI: 10.5194/bg-10-1155-2013
|View full text |Cite
|
Sign up to set email alerts
|

An unknown oxidative metabolism substantially contributes to soil CO<sub>2</sub> emissions

Abstract: Abstract. The respiratory release of CO2 from soils is a major determinant of the global carbon cycle. It is traditionally considered that this respiration is an intracellular metabolism consisting of complex biochemical reactions carried out by numerous enzymes and co-factors. Here we show that the endoenzymes released from dead organisms are stabilised in soils and have access to suitable substrates and co-factors to permit function. These enzymes reconstitute an extracellular oxidative metabolism (EXOMET) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 39 publications
6
57
0
Order By: Relevance
“…Previously, persistent CO 2 release from soil with eliminated or inhibited respiration was attributed to abiotic processes (Rozycki and Bartha, 1981;Trevors, 1996) and extracellular oxidative metabolism (Maire et al, 2013). Our data clearly demonstrate that inhibition of electron transport chain cannot stop intracellular glucose metabolism: microorganisms circumvent respiration inhibition via temporary extracellular electron transfer, giving organisms a chance to reconstruct new electron transport chains and resume normal (aerobic) respiration.…”
Section: Adaptation Mechanisms To Respiration Inhibitionsupporting
confidence: 57%
See 3 more Smart Citations
“…Previously, persistent CO 2 release from soil with eliminated or inhibited respiration was attributed to abiotic processes (Rozycki and Bartha, 1981;Trevors, 1996) and extracellular oxidative metabolism (Maire et al, 2013). Our data clearly demonstrate that inhibition of electron transport chain cannot stop intracellular glucose metabolism: microorganisms circumvent respiration inhibition via temporary extracellular electron transfer, giving organisms a chance to reconstruct new electron transport chains and resume normal (aerobic) respiration.…”
Section: Adaptation Mechanisms To Respiration Inhibitionsupporting
confidence: 57%
“…Increased 13 C recovery and reduced total CO 2 after NaN 3 inhibition could not be explained by a shift towards fermentative metabolism resulting from respiration inhibition, as 13 CO 2 from fermentation would be C-4 dominated instead of C-1. High CO 2 emission from soils with minimized microbial activity can be attributed to release of active oxidative extracellular enzymes (EXOMET) from dead organisms (Maire et al, 2013). To prove or reject the relevance of EXOMET compared with cellular metabolism, investigation of intracellularly formed metabolites (that is, de novo formed microbial biomass) was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of liquid water required for maintaining such biological activity, including thiocyanate hydrolase activity, could be extremely small and still result in a detectable amount of COS 30 emitted. In addition, Maire et al (2013) showed that endoenzymes released from dead organisms were stabilised in soils and could still lead to extracellular oxidative metabolism. This could also partly explain the continuation of COS production even at very low water content in our soils.…”
Section: Drivers and Mechanisms Of Cos Production Across European Soimentioning
confidence: 99%